2022
DOI: 10.1111/ffe.13668
|View full text |Cite
|
Sign up to set email alerts
|

Interaction analysis between strain concentration and strain localization in cracked body

Abstract: The appearance of strain localization (SL) in front of the crack tip is a factor that promotes transition toward the fatigue crack extension mode. Therefore, to predict fatigue crack extension behavior in case multiple modes occur, it is necessary to evaluate the degree of SL. In this study, the following simulations were performed on a single-crystal twinning-induced plasticity (TWIP) steel:(a) SL characterization by crystal plasticity finite element method (CPFEM) analysis of a smooth specimen under tension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Since the symmetry constraints are met, a quarter of the model is used, as shown in Figure 2B, to reduce the solving cost. 20 The total number of elements in this model is 256,000. Moreover, this specimen is the same type as the 2D smooth specimen.…”
Section: Cracked Specimenmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the symmetry constraints are met, a quarter of the model is used, as shown in Figure 2B, to reduce the solving cost. 20 The total number of elements in this model is 256,000. Moreover, this specimen is the same type as the 2D smooth specimen.…”
Section: Cracked Specimenmentioning
confidence: 99%
“…A ratio to indicate the strain localization behavior during tensile loading was proposed by Li et al 20 Strain localization means the local strain is higher than in other areas. The necking area is the area with the highest strain localization.…”
Section: Materials Index For Slsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] Recently, Verma et al 19 and Suzuki et al 20 found that strain distribution around the crack tip, fatigue limit, and crack extension mode for the metals susceptible to strain localization differs from those of the metals that are unsusceptible to strain localization. Li et al 21 proposed a new strain localization parameter to quantify the susceptibility of strain localization for the metal. Therefore, strain localization should be considered a material property of the metal.…”
Section: Introductionmentioning
confidence: 99%